2017
DOI: 10.1111/irv.12448
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of influenza a molecular viral shedding in Hutterite communities

Abstract: BackgroundPatterns of influenza molecular viral shedding following influenza infection have been well established; predictors of viral shedding however remain uncertain.ObjectivesWe sought to determine factors associated with peak molecular viral load, duration of shedding, and viral area under the curve (AUC) in children and adult Hutterite colony members with laboratory‐confirmed influenza.MethodsA cohort study was conducted in Hutterite colonies in Alberta, Canada. Flocked nasal swabs were collected during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Given that rhinovirus causes similar upper respiratory tract symptoms as influenza, we used the same parameterization for these two pathogens for volume of fluid excretion and number of shedding events, but influenza had a higher concentration per shedding event. While viral shedding rates were similar for all age groups for both rhinovirus and norovirus, very young children (< 1 year) had higher influenza shedding rates [25][26][27]. Betweenindividual shedding rates were high among young children and we were only able to find estimates from one small study, which suggested that young children might shed up 2 orders of magnitude more than older individuals [25].…”
Section: Literature Reviewmentioning
confidence: 63%
“…Given that rhinovirus causes similar upper respiratory tract symptoms as influenza, we used the same parameterization for these two pathogens for volume of fluid excretion and number of shedding events, but influenza had a higher concentration per shedding event. While viral shedding rates were similar for all age groups for both rhinovirus and norovirus, very young children (< 1 year) had higher influenza shedding rates [25][26][27]. Betweenindividual shedding rates were high among young children and we were only able to find estimates from one small study, which suggested that young children might shed up 2 orders of magnitude more than older individuals [25].…”
Section: Literature Reviewmentioning
confidence: 63%
“…There were more visitors and infected patients in the pediatric than the adult patient rooms which could possibly contribute to a higher viral load in the pediatric environment. Some studies postulated children may be more infectious than adults by longer duration of virus shedding 13 or increased peak viral load, but a systematic review found no difference in quantity of virus RNA in respiratory swabs by age 29,30 …”
Section: Discussionmentioning
confidence: 99%
“…This masking of gene expression biomarkers will reduce the predictive accuracy of point-of-care devices. While clinical symptoms, such as disease severity and presence of pneumonia, and demographic data, such as age and presence of comorbidities, are correlates of length of shedding (27)(28)(29)(30)(31), many of these clinical disease correlates of medically attended influenza do not manifest until many days after infection and have limited prognostic value. In contrast, significant differential PBL gene expression can be observed before 48 h postexposure just as symptoms are beginning to appear.…”
Section: Discussionmentioning
confidence: 99%